Anger and worry are related to problematic smartphone use: A cross-sectional examination of novel psychopathological constructs in a college-aged sample in the United Arab Emirates - Zahir Vally (Heliyon, 2022)
Introduction: Problematic smartphone use (PSU) has consistently been shown to be associated with depression and anxiety. However, the association of PSU and psychological constructs beyond these two have rarely been subjected to examination. Worry and anger are transdiagnostic constructs that, given their conceptual similarity with depression and anxiety, may similarly evidence significant relationships with PSU. Methods: To test these hypotheses, a sample of 264 college-aged students were recruited from a university in the United Arab Emirates. The sample ranged in age from 18 to 36 years (M = 21.51, SD = 2.99). Self-report measures of PSU, worry and anger were administered. Results: Results revealed statistically significant associations with PSU, anger, and worry – these results were evident following correlational as well as regression analyses. Moreover, using a recommended cut-off score from the literature to identify participants scoring beyond the clinical threshold indicative of PSU, worry and anger scores were significantly higher in the clinical sub-group. Conclusions: This study's results lend additional credibility to uses and gratifications theory and compensatory internet use theory as it appears that the excessive use of technologies may indeed serve the purpose of compensating for the management of emotional distress. Results are discussed within the context of these two theories.